Levantamento dos parâmetros físicos e químicos das águas dos lagos Bolonha e Água Preta, Belém - Pará - BARRETO, Lidianne Pereira Gomes Lucas (2019)
The Metropolitan Area includes the municipalities Belém, Marituba, Santa Isabel, Ananindeua, Santa Bárbara, and Benevides. The public water supply 75% of the metropolitan population is realized through the lakes Bolonha and Água Preta. Due to the importance of lakes in the region, this monograph realized a literature review of existing research in lakes considering the physical parameters (temperature, turbidity, color, transparency), chemical (dissolved oxygen, pH, chloride, ammonia-N, phosphate and chlorophyll), analysis of suspended solids and calculate and trophic, characterization realized in two distinct periods: one during the rainy season and another during less rainy or dry. Because of the points where the collections were made, the methods and equipment that the researchers used in the work presented similarly, it was possible to develop a database with the results. Through the literature review we obtained the conclusion that the rainfall in the region, the movement waters the river Guamá causes the lake Água Preta, the human actions exert great influences on the parameters. Some nutrients such as nitrate, ammonia- N, phosphate and chloride showed variations in their values over the years, probably due to the pollution load from domestic sewage released near the source. The parameters turbidity, ammonia-N and nitrate are in accordance with Resolution CONAMA 357/05 destined for class II water bodies (of which belong to the wellsprings of Utinga), this did not occur with the parameters dissolved oxygen and hydrogen potential. This resolution does not provide values for the parameters temperature, apparent color, phosphate, transparency, chloride and suspended solids. From the data obtained it was possible to observe a small change in environmental conditions of the wellsprings of Utinga. The literature review provides an analysis of the changes that are occurring and possible preventive measures to be put into practice as a way to protect the natural lakes Bolonha and Água Preta.